BSE Practice and BSE Self-Efficacy among Nursing Students in Aceh, Indonesia - Juanita, Juanita; Jittanoon, Piyanuch; Boonyasopun, Umaporn (Nurse Media Journal of Nursing, 2013)
Purpose: To survey the level of BSE practice among female nursing students in Aceh, and the degree of self-efficacy in those who did practice it.Method: Seventy-six nursing students from the Public Nursing College, Syiah Kuala University in Aceh who met the inclusion criteria were recruited. Stratified proportionate random sampling was used to determine the required number of first, second, and third year students. BSE self-efficacy of the students was measured by the BSE Self-Efficacy Questionnaire which was modified from an existing tool developed by Khatun (2010). In addition, the students’ doing BSE or not was measured by BSE Practice Questionnaire which was developed by the researcher. The data were analyzed by using descriptive statistics.Result: Only 39.5% of the students practiced BSE with more than half of the students saying they did not practice BSE (60.5%). The main factors that influenced the students’ performing BSE were not having a family history of breast cancer, single, and no history of breast illness. Among the thirty students who practiced BSE, most of them did not practice it routinely (70%), nor at the correct time (86.7%), and their confidence in performing BSE was at a moderate level overall, with a high level for BSE procedural efficacy and moderate level for barrier management efficacy.Conclusion: A majority of the Acehnese nursing students did not practice BSE, and those who did had only a moderate level of BSE self-efficacy. Therefore, the results of this study suggest emphasizing the need to teach nursing students about BSE in their undergraduate courses, with future follow-up research regarding the success of the educational program.Keywords: practice, self-efficacy, breast self-examination (BSE), nursing students